2010
DOI: 10.1186/1475-925x-9-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-rigid registration of breast surfaces using the laplace and diffusion equations

Abstract: A semi-automated, non-rigid breast surface registration method is presented that involves solving the Laplace or diffusion equations over undeformed and deformed breast surfaces. The resulting potential energy fields and isocontours are used to establish surface correspondence. This novel surface-based method, which does not require intensity images, anatomical landmarks, or fiducials, is compared to a gold standard of thin-plate spline (TPS) interpolation. Realistic finite element simulations of breast compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In [63, 65], the solution to Laplace’s equation along the organ surface was generated to extrapolate boundary conditions into the flanking and posterior regions. Components of this approach have been used to assist in non-rigid surface registration of the breast where fiducials were not present [72]. Upon completion of the solution of Laplace’s equation, the boundary conditions assigned to the posterior regions also undergo a norm-sensed application direction change.…”
Section: Methodsmentioning
confidence: 99%
“…In [63, 65], the solution to Laplace’s equation along the organ surface was generated to extrapolate boundary conditions into the flanking and posterior regions. Components of this approach have been used to assist in non-rigid surface registration of the breast where fiducials were not present [72]. Upon completion of the solution of Laplace’s equation, the boundary conditions assigned to the posterior regions also undergo a norm-sensed application direction change.…”
Section: Methodsmentioning
confidence: 99%
“…Both methodologies required conditions to be manually specified to various regions of the mesh. While the results presented by Ong et al [11] indicated better performance via the Laplacian method, the diffusion method did not require the difficult task of assigning a boundary condition to the chest wall in both pre-and postdeformed mesh domains. These methods, as well as the TPS method, will be compared to the intensitybased approach in this paper.…”
Section: Introductionmentioning
confidence: 92%
“…As described in [11], the phantom used in this study (hereafter referred to as Phantom 1) was created from an 8% w/v solution of polyvinyl alcohol (Flinn Scientific, Batavia, IL) in an anthropomorphic breast mold. To provide intrinsic fiducial markers, 34 1-mm stainless steel beads were distributed over the phantom directly under its surface.…”
Section: Phantom Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have demonstrated that numerical modeling can be used to predict the extent of electroporation in biological tissues [ 57 - 64 ]. Also, numerical modeling and optimization have already been used for optimization of electric pulse parameters for electrochemotherapy of subcutaneous tumors, for tumor ablation with irreversible electroporation [ 63 , 65 - 67 ] and recently, the first deep-seated tumor was treated with electrochemotherapy based on a numerical treatment plan [ 68 ]. However, up to now there exists no such study which would use numerical modeling for optimization of gene electrotransfer.…”
Section: Introductionmentioning
confidence: 99%